Fashion theory an introduction - Barnard, Malcolm (Routledge, 2014)
Fashion is both big business and big news. From models'eating disorders and sweated labour to the glamour of a new season's trends, statements and arguments about fashion and the fashion industry can be found in every newspaper, consumer website and fashion blog. Books which define, analyse and explain the nature, production and consumption of fashion in terms of one theory or another abound. But what are the theories that run through all of these analyses, and how can they help us to understand fashion and clothing? Fashion Theory: an introduction explains some of the most influential and important theories on fashion: it brings to light the presuppositions involved in the things we think and say about fashion every day and shows how they depend on those theories. This clear, accessible introduction contextualises and critiques the ways in which a wide range of disciplines have used different theoretical approaches to explain – and sometimes to explain away – the astonishing variety, complexity and beauty of fashion. Through engaging examples and case studies, this book explores: fashion and clothing in history fashion and clothing as communication fashion as identity fashion, clothing and the body production and consumption fashion, globalization and colonialism fashion, fetish and the erotic. This book will be an invaluable resource for students of cultural studies, sociology, gender studies, fashion design, textiles or the advertising, marketing and manufacturing of clothes.